2023
DOI: 10.1007/s10668-023-03005-6
|View full text |Cite
|
Sign up to set email alerts
|

Social Life Cycle Assessment in the Construction Industry: Systematic Literature Review and Identification of Relevant Social Indicators for Carbon Reinforced Concrete

Abstract: This article deals with the application of social life cycle assessment (S-LCA) in the construction sector and explicitly focuses on carbon reinforced concrete (CRC). The publication consists of two parts: (1) a scientific literature review on the current implementation of S-LCA in the construction sector, and (2) the definition of the relevant social hotspots for the cradle-to-gate production of CRC. The literature review was conducted to provide a general overview and compare S-LCA studies in the constructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Furthermore, social assessment is often neglected in the road sector since only a few stand-alone S-LCA studies exist in the literature [22,164]. This finding is consistent with similar observations in the construction industry [165]. Less than half of the reviewed publications applied S-LCA to assess social impacts.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, social assessment is often neglected in the road sector since only a few stand-alone S-LCA studies exist in the literature [22,164]. This finding is consistent with similar observations in the construction industry [165]. Less than half of the reviewed publications applied S-LCA to assess social impacts.…”
supporting
confidence: 65%
“…S-LCA enables the consideration of all relevant stakeholders and the consistent application of a life cycle approach equivalent to LCA and LCC. Moreover, only a few of the reviewed studies considered the stakeholder category of workers, although relevant construction sector issues include workers' working conditions and health and safety [165]. In the reviewed studies, workers were only considered during the construction stage.…”
mentioning
confidence: 99%
“…To prove the applicability of the LCSA-Wheel and provide a short example, an implementation of LCSA results for carbon reinforced concrete based on previous studies [30,31] is conducted in the following. The system boundary is defined as cradle-to-gate, and the functional unit is defined as a double wall made of carbon reinforced concrete-based on and as a continuation of a previous LCA.…”
Section: Practical Example Of Carbon Reinforced Concretementioning
confidence: 99%
“…In S-LCA studies, OHS belongs to the most considered stakeholder category [19] and is one of the most considered impact subcategories [20,21]. Recent S-LCA reviews about the agri-food [22], solid waste management [20], and biofuel [21] sectors found that most studies follow a mixed approach where quantitative and qualitative data are collected but organizations have difficulties in collecting OHS data [23]. Following the Type I approach results in selecting OHS indicators about (1) policy concerning health and safety; (2) general occupational safety measures; (3) preventive measures and emergency protocols for accidents and injuries; and (4) appropriate protective gear required, which are assessed with a 0-5 or 0-4 point index [24][25][26].…”
Section: Introductionmentioning
confidence: 99%